2011
DOI: 10.1161/hypertensionaha.110.168252
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Training–Induced Left Ventricular Hypertrophy Involves Regulatory MicroRNAs, Decreased Angiotensin-Converting Enzyme-Angiotensin II, and Synergistic Regulation of Angiotensin-Converting Enzyme 2-Angiotensin (1-7)

Abstract: Aerobic exercise training leads to a physiological, non pathological left ventricular hypertrophy (LVH); however, the underlying biochemical and molecular mechanisms of physiological LVH are unknown. The role of microRNAs regulating the classic and the novel cardiac renin angiotensin system (RAS) was studied in trained rats assigned to three groups: sedentary, swimming trained with protocol 1 (T1: moderate volume training) and protocol 2 (T2: high volume training). Cardiac Ang I levels, ACE activity and protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
136
1
21

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 203 publications
(168 citation statements)
references
References 45 publications
10
136
1
21
Order By: Relevance
“…Interestingly, in a recent study (41) we showed that cardiac AGT and Ang I levels, ACE activity and protein expression, as well as Ang II levels were lower in swimming-trained rats, although AT1 receptor levels increased after training. In addition, ACE2 and Ang (1-7) levels were increased in the hearts of swimming-trained rats.…”
Section: Exercise-induced Cardiac Hypertrophy Via At1 Receptormentioning
confidence: 77%
See 2 more Smart Citations
“…Interestingly, in a recent study (41) we showed that cardiac AGT and Ang I levels, ACE activity and protein expression, as well as Ang II levels were lower in swimming-trained rats, although AT1 receptor levels increased after training. In addition, ACE2 and Ang (1-7) levels were increased in the hearts of swimming-trained rats.…”
Section: Exercise-induced Cardiac Hypertrophy Via At1 Receptormentioning
confidence: 77%
“…Interestingly, we recently showed that AT1 receptor blockade prevents physiological left ventricle hypertrophy induced by resistance training (17) and aerobic exercise training (19,41). These studies underscore the importance of a better understanding of aerobic and resistance training and the regulation of left ventricle hypertrophy by the RAS (Figure 2).…”
Section: Exercise-induced Cardiac Hypertrophy Via At1 Receptormentioning
confidence: 83%
See 1 more Smart Citation
“…Among the autonomic and hemodynamic adaptations which will influence the cardiovascular system, resting bradycardia consists in a good functional parameter to verify the adaptation and efficiency of the aerobic ET; therefore, it is considered an ET physiological marker. This adaptation is observed both in experimentation animals 20,21,23 and humans 24 .…”
Section: Discussionmentioning
confidence: 72%
“…This training protocol with increase of exercise volume has been used with the purpose to mimic a high-performance exercise training 21 . The used protocols were characterized as low and moderate intensity and long duration trainings, being efficient in promoting cardiovascular adaptations and increase of muscular oxidative capacity 20,21 . Pre and post the ET period, the animals were submitted to hemodynamic analyses, exercise tolerance test and oxygen uptake peak.…”
Section: Protocols Of Aerobic Physical Trainingmentioning
confidence: 99%